2021
DOI: 10.21580/pjpp.v6i1.6679
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gender differences in the vulnerability towards drug abuse among adolescents in Malaysia

Abstract: Protective and risk factors are important in reducing vulnerability towards drug abuse among adolescents. This study, therefore, aims to explore gender differences in such vulnerability in high-risk areas identified by the National Anti-Drugs Agency Malaysia. The study employs a survey design, with questionnaires distributed to 213 adolescents who fulfilled the inclusion criteria. The researchers developed the questionnaire and comprised five parts: the demographic profile, interpersonal conflict, negative emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Sulaiman et al (2021) study results show that adolescents need a social supporting environment, such as strong family relationships, positive peer influence, and good role models. All those components can provide them with protective factors to prevent them from becoming involved in risky behavior such as substance use disorder.Taylor(2003) andWeiten (2011) explain that when someone is experiencing problems or stress, the brain sends signals along two lines.…”
mentioning
confidence: 87%
“…Sulaiman et al (2021) study results show that adolescents need a social supporting environment, such as strong family relationships, positive peer influence, and good role models. All those components can provide them with protective factors to prevent them from becoming involved in risky behavior such as substance use disorder.Taylor(2003) andWeiten (2011) explain that when someone is experiencing problems or stress, the brain sends signals along two lines.…”
mentioning
confidence: 87%
“…Hasani et al (2021) reported that drug abusers increased from 1.5% to 3.4% between 2012 and 2017. The number of drug users in 2017 was 12,089, increasing to 12,520 in 2018 (Sulaiman et al, 2021). Cheah et al (2020) reported that in 2017, 33,500 of the 59,600 convicts in prison in Malaysia were there because of drug abuse offences.…”
Section: Literature Reviewmentioning
confidence: 99%